POTENSI BIOMASSA DAN KARBON PADA HUTAN TANAMAN Eucalyptus pellita PT. FINNANTARA INTIGA KABUPATEN SINTANG - Dewi, Rahayu; Gusti, Hardiansyah; Ganjar, Widhanarto Oki (JURNAL HUTAN LESTARI, 2013)
The purpose of this research was to estimate biomass and stored carbon in the forest of Eucalyptus pellita and its potency to adsorb atmospheric CO2. The allometric equation was then developed based on growth dimension and tree volume. Method that utilized is survey's method asosiatif's descriptive by gathers height data and diameter of Eucalyptus pellita one that available at HTI PT. Finnantara Intiga Kabupaten Sintang, 1, 2, 4, and 5 years old. Develop allometric's equation utilizes to methodic regression. The result show that the potential average biomass in stands of Eucalyptus pellita are 69,392 tons C/ha. While the potential of Eucalyptus pellita stands to absorb atmospheric CO2 ranges from 3,783 135,128 tons/ha/years. To estimate relationship betwen diameter and biomass of tree of Eucalyptus pellita, the developed allometric equations is Y=6.622D5,306 , relationship betwen diameter and tree carbon is Y=2.980D5,306, relationship betwen diameter and absorb CO2 (g) is Y=10.940D5,306 with R2=95,2%. While relationship betwen volume and biomass is Y=1,235V0,997, relationship betwen volume and tree carbon is Y=0,556V0,997, and relationship betwen volume and absorb CO2 (g) is Y=2,040V0,997 with R2=99,9%. Keywords : Eucalyptus pellita , biomass, carbon, allometric